Accuracy of conventional digital palpation and ultrasound of the cricothyroid membrane in obese women in labour. (17th July 2015) - You‐Ten, K. E.; Desai, D.; Postonogova, T.; Siddiqui, N.
Summary Success of cricothyroidotomy depends on accurate identification of anatomical neck landmarks. Anaesthetists palpated the cricothyroid membrane of 28 obese and 28 non‐obese women in labour (cut‐off BMI 30 kg.m−2) and marked the entry point for device insertion with an ultraviolet invisible pen. Ultrasonography was used to mark the midpoint of the cricothyroid membrane and the distance between the two marks was measured. The median (IQR [range]) distance between the two marks was significantly greater in the obese than the non‐obese patients (5 (2–9.5 [0–34]) mm vs 1.8 (0.1–6 [0–15]) mm, respectively; p = 0.02). The cricothyroid membrane was accurately identified with digital palpation in only 39% (11/28) of obese compared with 71% (20/28) of non‐obese patients (p = 0.03). Increased neck circumference in obese patients was significantly associated with inaccuracy in locating the cricothyroid membrane. Percutaneous identification of the cricothyroid membrane in obese women in labour was poor. Pre‐procedural ultrasound may help improved the identification of neck landmarks for cricothyroidotomy.